PENGARUH PELATIHAN DAN PENERAPAN MODEL METODE ASUHAN KEPERAWATAN PROFESIONAL (MAKP) PRIMARY NURSING TERHADAP KUALITAS ASUHAN KEPERAWATAN DI RUMAH SAKIT KOTA MEDAN - Hendry Kiswanto Mendrofa; Lammurni Sagala (Universitas Murni Teguh, 2019)
Improving quality nursing care has become a major concern for all professional health care providers and consumers, research and literature on the quality of providing nursing care is still underdeveloped, especially in Indonesia. The model of primary nursing care (MAKP) nursing method is an assignment method where nurses are responsible to patients for 24 hours from the time the patient enters into discharge, this method embodies the independence of the nurses in implementing care and the model of primary nursing care (MAKP) method of nursing can increase the quality of nursing care services, the purpose of this study was to analyze the effect of the model of primary nursing care (MAKP) primary nursing methods on the quality of nursing care. This research is a Quasi Experimental Study with non-equivalent control group pretest-posttest design that is observing the effect of using the intervention and control groups without subject randomization. The population in this study were nurses who worked in inpatient and inpatient installations, the sampling technique in this study used purposive sampling technique. Data collection on the quality of nursing care using the Patient's Assessment of Quality Scale - Acute Care Version (PAQS-ACV) instrument, based on the results of the Content Validity Index (CVI) test of the Patient's Assessment of Quality Scale - Acute Care Version (PAQS-ACV) instrument was 0.98 and the results The reliability test of the Patient's Assessment of Quality Scale - Acute Care Version (PAQS-ACV) questionnaire obtained a Cronbach Alpha value of 0.66. The results showed that there was an influence on the application of the primary nursing care professional model (MAKP) primary nursing on improving the quality of nursing care, based on the results of the independent t-test, it was found that the sig (2-tailed) value was 0.00 where <0.05, it could be concluded that there were differences Significant between the quality of nursing care in the intervention group with the quality of nursing care in the control group, it is recommended that all hospitals, especially in North Sumatra, apply the model of primary nursing care method (MAKP) in primary nursing in the implementation of nursing duties in the inpatient room. Abstrak Meningkatkan asuhan keperawatan yang berkualitas telah menjadi perhatian utama bagi semua penyedia layanan kesehatan profesional dan konsumen, penelitian dan literatur tentang kualitas pemberian asuhan keperawatan masih belum berkembang khususnya di Indonesia. Model metode asuhan keperawatan (MAKP) primary nursing merupakan metode penugasan dimana perawat bertanggung jawab kepada pasien selama 24 jam mulai saat pasien masuk sampai dengan keluar, metode ini mewujudkan kemandirian para perawat dalam melaksakan asuhan dan model metode asuhan keperawatan (MAKP) primary nursing dapat meningkatkan kualitas pelayanan asuhan keperawatan, Tujuan dari penelitian ini adalah menganalisis pengaruh model metode asuhan keperawatan profesional (MAKP) primary nursing terhadap kualitas asuhan keperawatan. Penelitian ini merupakan jenis penelitian Quasi Exsperimental Study dengan desain pretest-posttest non equivalent control group yaitu mengobservasi pengaruh dengan menggunakan kelompok intervensi dan kontrol tanpa randomisasi subjek. Populasi dalam penelitian ini yaitu perawat yang bekerja di instalasi rawat inap dan pasien rawat inap, teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling. Pengumpulan data kualitas asuhan keperawatan menggunakan instrumen Patient’s Assessment of Quality Scale – Acute Care Version (PAQS-ACV), berdasarkan hasil uji Content Validity Index (CVI) instrumen Patient’s Assessment of Quality Scale – Acute Care Version (PAQS-ACV) adalah 0.98 dan hasil uji reliabilitas kuesioner Patient’s Assessment of Quality Scale – Acute Care Version (PAQS-ACV) didapatkan nilai Cronbach Alpha yaitu 0,66. Hasil penelitian menunjukkan bahwa ada pengaruh penerapan model metode asuhan keperawatan profesional (MAKP) primary nursing terhadap peningkatan kualitas asuhan keperawatan, berdasarkan hasil uji independend t-test di ketahui nilai sig (2-tailed) sebesar 0.00 dimana < 0.05 maka dapat disimpulkan bahwa ada perbedaan yang signifikan antara kualitas asuhan keperawatan pada kelompok intervensi dengan kualitas asuhan keperawatan pada kelompok kontrol, disarankan untuk seluruh rumah sakit khususnya wilayah sumatera utara menerapkan model metode asuhan keperawatan profesional (MAKP) primary nursing dalam pelaksanaan tugas keperawatan diruang rawat inap.